2021
DOI: 10.1093/chromsci/bmab066
|View full text |Cite
|
Sign up to set email alerts
|

New Methodology to Study the Dispersive Component of the Surface Energy and Acid–Base Properties of Silica Particles by Inverse Gas Chromatography at Infinite Dilution

Abstract: A new methodology was proposed to determine the dispersive component of the surface energy ${\gamma}_s^d$ of a solid taking into account the effect of the temperature on the surface area of n-alkanes, methylene group (${a}_{- CH2-}$) and polar molecules, thus defeating the method used by Dorris–Gray Schultz et al. We determined the correct ${\gamma}_s^d$ of the surface energy, the specific free energy, enthalpy and entropy of adsorption of polar molecules as well as the acid base constants of silica particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(88 citation statements)
references
References 94 publications
0
88
0
Order By: Relevance
“…Knowing Δ H a sp and the normalized donor DN′ and acceptor AN′ numbers of electrons of the various probes, one obtained the acid K A and base K D constants of the solid surfaces from eq . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing Δ H a sp and the normalized donor DN′ and acceptor AN′ numbers of electrons of the various probes, one obtained the acid K A and base K D constants of the solid surfaces from eq . …”
Section: Methodsmentioning
confidence: 99%
“…The effect of OAN on the surface energy of p -HPA has been evaluated. The dispersive surface free energy component is the most important physical parameter. The London dispersive surface free energy component γ s d ( T ) as a function of temperature has been assessed by using nine different models all based on the Fowkes relation. Two models, the Dorris–Gray relation and Hamieh–Dorris–Gray model and six models, the Kiselev, cylindrical, geometric, spherical, van der Waals and Redlich–Kwong–Hamieh models have been applied using six molecular methods for determining the surface areas of organic molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Where xi is a thermodynamic parameter relative to the organic solvents and ai and bi are constants relative to the probes. The physicochemical variable xi can be one of the following parameters: vapor pressure P0, 15 boiling point BP , 14 deformation polarizability α0, 16 standard enthalpy of vaporization Hitalicvap0, 18 enthalpy of vaporization HitalicvapT depending on the temperature, 12 topological index χT, 17 standard enthalpy of formation Hf0 of organic solvents 12 …”
Section: Methodsmentioning
confidence: 99%
“…Hamieh's works 12,13,20–22 demonstrated that the surface area of organic molecules varies as a function of the temperature and showed an important dependence of the surface area of methylene group a –CH2– versus the temperature. Recently, in a recent paper, Hamieh 12 gave an expression of aCH2T (in Å 2 with T in K ): aCH2T=69.939563.02T1/2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation